A shift in coronary care unit patient population: Ten year experience from an urban tertiary care center. (2nd October 2015) - Krepp, Joseph M.; Hebsur, Shrinivas; Panza, Julio A.; Cooper, Howard A.; Asch, Federico M.
Abstract : The need for cardiovascular expertise in the treatment of advanced heart failure (AHF), malignant arrhythmias, and structural heart disease has shifted the role of the CCU to a more diverse and medically complex patient population. This study's purpose was to analyze the temporal trends in the principal diagnosis leading to admission to the CCU in a tertiary referral hospital. Over the last 15 years, the CCU has evolved from a medical unit strictly focusing on the care of patients with ACS to an advanced cardiac intensive care unit. The trends observed at our center provide further evidence that today's CCU contains a broader, more complex, critically-ill patient population.